(untitled) (Revista de História da UEG (REVHIST), 2021)
The article analyzes how the transformations of cultural notion in the curricular document of Basic Education in Angola and the impact that these discourses have in allowing a rupture to break with a traditional culture, historically thought to shape in the form of practices, subjectivations, and government in social relations. The study uses qualitative research through document analysis. It was concluded that the curriculum documents implemented in 2013 break with the thought traditionally constructed thinking between 1975 and 2001 about cultural unity, elimination of the difference sedimented by prejudice and ethnic division. These new discourses mobilize dialogue and tolerance towards with one another in the school environment. Keywords: Culture. Primary school. Curriculum. Subject. Angola.